2007
DOI: 10.1016/j.biomaterials.2007.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of bacterial adhesion and biofilm formation on zwitterionic surfaces

Abstract: In this work, we report a study of long-chain zwitterionic poly(sulfobetaine methacrylate) (pSBMA) surfaces grafted via atom transfer radical polymerization (ATRP) for their resistance to bacterial adhesion and biofilm formation. Previously, we demonstrated that p(SBMA) is highly resistant to nonspecific protein adsorption. Poly(oligo(ethylene glycol) methyl ether methacrylate) (pOEGMA) grafted surfaces were also studied for comparison. Furthermore, we quantify how surface grafting methods will affect the long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
591
2
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 661 publications
(616 citation statements)
references
References 36 publications
(63 reference statements)
16
591
2
7
Order By: Relevance
“…Comparison with the performance of our hits to these literature reports is difficult as experimental methodologies vary widely. Attachment of P. aeruginosa (PA01) after 3 h incubation on a poly(sulfobetaine methacrylate)-grafted surface has been reported to be lower by 25-fold compared to that on glass 19 , and in an incubation time closer to ours, a poly(carboxybetaine methacrylate)-grafted surface had 11-fold lower attachment of P. aeruginosa after 96-h bacterial exposure compared to glass 18 .…”
Section: Development Of Medical Device Coatingssupporting
confidence: 49%
See 2 more Smart Citations
“…Comparison with the performance of our hits to these literature reports is difficult as experimental methodologies vary widely. Attachment of P. aeruginosa (PA01) after 3 h incubation on a poly(sulfobetaine methacrylate)-grafted surface has been reported to be lower by 25-fold compared to that on glass 19 , and in an incubation time closer to ours, a poly(carboxybetaine methacrylate)-grafted surface had 11-fold lower attachment of P. aeruginosa after 96-h bacterial exposure compared to glass 18 .…”
Section: Development Of Medical Device Coatingssupporting
confidence: 49%
“…There are several other different strategies that can be found in the literature to reduce bacterial attachment to surfaces that are not yet commercially available; for example, zwitterionic coatings function by preventing attachment 18,19 . Comparison with the performance of our hits to these literature reports is difficult as experimental methodologies vary widely.…”
Section: Development Of Medical Device Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the degradation of the ethylene-glycol-containing chemistries makes them unsuitable for long-term antifouling applications [34,35]. Other promising approaches involve the use of amphiphilic [26,27,29,36] or zwitterionic chemistries [37][38][39][40]. Even though fouling inhibition is the most desirable way of avoiding biofouling, the development of such inert, non-toxic, and long-term stable coatings remains to be the most challenging of the three approaches.…”
Section: Biofouling Research: the Quest For Environmentallymentioning
confidence: 99%
“…was observed that for 80% of the successfully predicted cases, the impact of the tested variables at 0.5 h (initial adhesion) was further amplified during the biofilm maturation phase (after 6 h). Different studies have shown that lower initial cell adhesion leads to lower amount of biofilm (Cheng et al, 2007;Godoy-Gallardo et al, 2014) whereas others report that these initial events are not always important for biofilm maturation (Bernstein et al, 2014;Cerca et al, 2005).…”
Section: Resultsmentioning
confidence: 99%